The MARVIN Hypothesis: Linking Unhealthy Lifestyles to Intracranial Aneurysm Rupture Risk and Clinical Prognosis - Vanessa M. Swiatek; Igor Fischer; Rajiv Khajuria; Amir Amini; Hannah Steinkusch; Ali Rashidi; Klaus-Peter Stein; Claudia A. Dumitru; I. Erol Sandalcioglu; Belal Neyazi (Medicina)
Background and Objectives: The rising incidence of modifiable lifestyle risk factors and cardiovascular diseases, driven by poor diet, inactivity, excessive alcohol use, and smoking, may influence the development and rupture of intracranial aneurysms (IA). This study aimed to examine the impact of lifestyle-related and cardiovascular risk factors on IA rupture and patient outcomes. Materials and Methods: We developed the “MARVIN” (Metabolic and Adverse Risk Factors and Vices Influencing Intracranial Aneurysms) model and conducted a retrospective analysis of 303 patients with 517 IAs, treated between 2007 and 2020. Of these, 225 patients were analyzed for rupture status and 221 for clinical outcomes. The analysis focused on hypertension, diabetes, hypercholesterolemia, vascular diseases, nicotine and alcohol abuse, obesity, aneurysm rupture status, and clinical outcomes. Logistic regression was used to evaluate the impact of these risk factors. Results: Among those with risk factors, 24.9% (56/225) and 25.3% (56/221) had one, 32.0% (72/225) and 30.8% (68/221) had two, 20.0% (45/225) and 20.4% (45/221) had three, 12.0% (27/225) and 12.2% (27/221) had four, 4.0% (9/225) and 4.1% (9/221) had five, 0.9% (2/225) had six in both groups, and 0.4% (1/225) and 0.5% (1/221) had seven risk factors, respectively. Strong relationships were found between lifestyle-related vascular risk factors, indicating multiple comorbidities in patients with unhealthy habits. Smokers with ruptured aneurysms had higher WFNS (World Federation of Neurosurgical Societies) scores, but nicotine abuse did not affect long-term outcomes. The most significant predictors for poor outcomes were WFNS score and age, while age and a history of vascular diseases were protective against rupture. Despite the high prevalence of modifiable risk factors, they did not significantly influence rupture risk. Conclusions: The findings suggest a need for multifactorial risk assessment strategies in managing IA patients. Future studies with larger cohorts are required to confirm these results and better understand IA progression.